The Influence of Organizational Culture, Managerial Ability, and Job Satisfaction on the Performance of Madrasa Superintendents of the Ministry of Religion of North Sumatra Province - Suhartono, Budi; Azmi, Fachruddin; Ananda, Rusydi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to; (1) Organizational Culture on Performance; (2) Organizational Culture on Satisfaction; (3) Ability to Performance; (4) Ability to Satisfaction; (5) Satisfaction with Performance (6) Simultaneous Organizational Culture and Ability with Performance; (7) Simultaneous Ability and Satisfaction with Performance; (8) Simultaneous Organizational Culture Capability and Satisfaction with Performance. Research method This research is a quantitative research with a survey research type, because it is carried out by using a questionnaire for the four variables given to respondents. The results of the research findings are as follows; (1) Organizational Culture on Satisfaction of 59.4%; (2) Ability to Satisfaction of 51.4%; (3) Organizational Culture on Performance of 67.4%; (4) Ability to Performance of 48.9%; (5) Satisfaction with Performance of 79.4%; (6) Organizational Culture and Ability to Performance of 23.9%; (7) Ability and Satisfaction with Performance of 63.9%; (8) Organizational Culture and Capability and Satisfaction with Performance of 70.0%.